Improvement in health expectancy at ages 50 and 65 in Denmark during the period 2004–2011. Issue 3 (May 2015) - Jeune, Bernard; Eriksen, Mette Lindholm; Andersen-Ranberg, Karen; Brønnum-Hansen, Henrik
Aims: In Denmark life expectancy (LE) has increased since 1995 after a long period of stagnation. Healthy life expectancy (HLE) at age 65 increased more than LE during the period 1987-2005. The aim of the study was to determine the trend in HLE in Denmark at ages 50 and 65 during the period 2004-2011. Methods: The study was based on nationwide register data on mortality and data on health status from the SHARE surveys carried out in 2004/2005, 2006/2007 and 2010/2011. Expected lifetime in various health states was estimated by Sullivan's method. Changes from 2004 to 2011 were decomposed into contributions from changes in mortality and prevalence of activity limitations. Results: During the period 2004-2011 LE increased by about 1 year at both age 50 and age 65. However, the increase in expected lifetime in self-rated good health, without long-term health problems and without activity limitations was even longer in both genders and it increased by 1.5-4.0 years depending on age, gender and health indicator. Consequently, expected lifetime in an unhealthy state decreased and the proportions of lifetime in a healthy state increased. The disability effect of the health gain was stronger than the mortality effect. Conclusions: In Denmark HLE increased substantially more than LE during the period 2004-2011 for all three health indicators at both age 50 and age 65, and for both genders. Thus, the improvement in health expectancy continued in Denmark in recent years.